2019
DOI: 10.1080/17441730.2019.1651573
|View full text |Cite
|
Sign up to set email alerts
|

The influence of premarital coresidence with parents and family income on the transition to first marriage in South Korea

Abstract: Premarital family context is influential for the transition to first marriage. This study examines the extent to which coresidence with parents and family income is associated with the transition to first marriage in South Korea. Drawing on extended coresidence perspective, the study examines the extent to which premarital coresidence with parents is associated with the transition to first marriage. Furthermore, the study examines the influence of family income and its moderating influence on the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The dramatic fertility decline has motivated a robust body of scholarship tracking the evolving impact of SES on marital outcomes among Korean men and women. Consistent with Western cases, past studies have found that different SES markers are positively associated with marriage for Korean men (Kim, 2017;Kim, 2020;Lee et al, 2021;Yoon et al, 2022). There is, however, limited consensus about how employment and education affect Korean women's marriage chances.…”
Section: Accounting For Marriage Decline In the East Vs The Westmentioning
confidence: 72%
See 4 more Smart Citations
“…The dramatic fertility decline has motivated a robust body of scholarship tracking the evolving impact of SES on marital outcomes among Korean men and women. Consistent with Western cases, past studies have found that different SES markers are positively associated with marriage for Korean men (Kim, 2017;Kim, 2020;Lee et al, 2021;Yoon et al, 2022). There is, however, limited consensus about how employment and education affect Korean women's marriage chances.…”
Section: Accounting For Marriage Decline In the East Vs The Westmentioning
confidence: 72%
“…Although several studies of marriage in different settings, including Korea, incorporate family background variables in quantitative analyses—father's occupation, mother's work status, father and mother's education, two‐parent households, etc. (Hu, 2016; Kim, 2017; Kim, 2020; Park, 2013; Raymo, 2003; Sweeney, 2002; Yu & Xie, 2015)—they seldom elaborate on the specific mechanisms through which parental socioeconomic resources matter for children's marriage outcomes. Instead, parental attributes are utilized as general proxies for overall resources that influence marital union.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations